Development and Evaluation of Real-Time PCR-Based Fluorescence Assays for Detection of Chlamydia pneumoniae - Tondella, Maria Lucia C. (American Society for Microbiology, 2002)
Chlamydia pneumoniae is an important respiratory pathogen recently associated with atherosclerosis and several other chronic diseases. Detection of C. pneumoniae is inconsistent, and standardized PCR assays are needed. Two real-time PCR assays specific for C. pneumoniae were developed by using the fluorescent dye-labeled TaqMan probe-based system. Oligonucleotide primers and probes were designed to target two variable domains of the ompA gene, VD2 and VD4. The limit of detection for each of the two PCR assays was 0.001 inclusion-forming unit. Thirty-nine C. pneumoniae isolates obtained from widely distributed geographical areas were amplified by the VD2 and VD4 assays, producing the expected 108- and 125-bp amplification products, respectively. None of the C. trachomatis serovars, C. psittaci strains, other organisms, or human DNAs tested were amplified. The amplification results of the newly developed assays were compared to the results of culturing and two nested PCR assays, targeting the 16S rRNA and ompA genes. The assays were compared by testing C. pneumoniae purified elementary bodies, animal tissues, 228 peripheral blood mononuclear cell (PBMC) specimens, and 179 oropharyngeal (OP) swab specimens obtained from ischemic stroke patients or matched controls. The real-time VD4 assay and one nested PCR each detected C. pneumoniae in a single, but different, PBMC specimen. Eleven of 179 OP specimens (6.1%) showed evidence of the presence of C. pneumoniae in one or more tests. The real-time VD4 assay detected the most positive results of the five assays. We believe that this real-time PCR assay offers advantages over nested PCR assays and may improve the detection of C. pneumoniae in clinical specimens.